2023
DOI: 10.3390/pr11051391
|View full text |Cite
|
Sign up to set email alerts
|

Product Yields Dependency on the Carbide Phase Presence in Cobalt and Iron SBA-15 Catalysts Structure in the Fischer–Tropsch Synthesis

Abstract: The use of carbide catalysts in Fischer–Tropsch synthesis (FTS) is an active area of research, as carbide phases have been shown to improve the stability and performance of catalysts in this reaction. This study compared the catalytic activity and product selectivity of cobalt and iron catalysts supported on SBA-15, with and without a carbide phase and reduction treatment before the reaction. Results showed that the presence of the carbide phase had a noticeable influence on the catalytic behavior of the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…After catalyst activation and CO hydrogenation reaction in the spent sample CoO (cubic), Ni (rhombohedral), Co 3 C (orthorhombic), NiC (cubic) and Co (cubic) phases were found. Assessment of XRD results showed that oxidic phases of fresh catalyst along with activation and FTS processes changed into carbide and metallic phases; it has been reported that these phases are active for FTS 35,36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After catalyst activation and CO hydrogenation reaction in the spent sample CoO (cubic), Ni (rhombohedral), Co 3 C (orthorhombic), NiC (cubic) and Co (cubic) phases were found. Assessment of XRD results showed that oxidic phases of fresh catalyst along with activation and FTS processes changed into carbide and metallic phases; it has been reported that these phases are active for FTS 35,36 …”
Section: Resultsmentioning
confidence: 99%
“…Assessment of XRD results showed that oxidic phases of fresh catalyst along with activation and FTS processes changed into carbide and metallic phases; it has been reported that these phases are active for FTS. 35,36 Scanning electron microscopy The SEM technique was employed for investigating the morphological characteristics and particle aggregation of samples.…”
Section: Catalyst Structural Characteristics X-ray Diffractionmentioning
confidence: 99%